Challenges and strategies in the soluble expression of CTA1-(S14P5)4-DD and CTA1-(S21P2)4-DD fusion proteins as candidates for COVID-19 intranasal vaccines. - Simson Tarigan; Gita Sekarmila; Apas; Sumarningsih; Ronald Tarigan; Riyandini Putri; Damai Ria Setyawati (PLoS ONE)
Developing intranasal vaccines against pandemics and devastating airborne infectious diseases is imperative. The superiority of intranasal vaccines over injectable systemic vaccines is evident, but developing effective intranasal vaccines presents significant challenges. Fusing a protein antigen with the catalytic domain of cholera toxin (CTA1) and the two-domain D of staphylococcal protein A (DD) has significant potential for intranasal vaccines. In this study, we constructed two fusion proteins containing CTA1, tandem repeat linear epitopes of the SARS-CoV-2 spike protein (S14P5 or S21P2), and DD. Structural predictions indicated that each component of the fusion proteins was compatible with its origin. In silico analyses predicted high solubility for both fusion proteins when overexpressed in Escherichia coli. However, contrary to these predictions, the constructs exhibited limited solubility. Lowering the cultivation temperature from 37°C to 18°C did not improve solubility. Inducing expression with IPTG at the early log phase significantly increased soluble CTA1-(S21P2)4-DD but not CTA1-(S14P5)4-DD. Adding non-denaturing detergents (Nonidet P40, Triton X100, or Tween 20) to the extraction buffer significantly enhanced solubility. Despite this, purification experiments yielded low amounts, only 1-2 mg/L of culture, due to substantial losses during the purification stages. These findings highlight the challenges and potential strategies for optimizing soluble expression of CTA1-DD fusion proteins for intranasal vaccines.